Implementation of Sufistic Counseling on Overcoming Game Online to Children at Kragan Village - Rochanah, Rochanah; Nabila, Sintya Ummu (CV. Creative Tugu Pena, 2022)
The application of Sufistic counseling is beneficial for individuals, especially in changing deviant behavior. As in the Kragan Village, many children experience problems, namely online game addiction which has a negative impact on their behavior, daily activities, emotional stability, and their socialization to the community environment. Solving their problem is very important for the development children when they grow up to adults. The article aims to analyze the application of sufistic counseling in overcoming onlinebgame addiction for children at Kragan Village. The researchers used is qualitative research by conducting direct interviews and observation. The results show that the application of Sufistic counseling to children in Kragan Village who are addicted to onlinegames in a way that counselors, the family environment, schools, and the community can provide direction and guidance in accordance with the Qur'an and Hadith. Hence, they would remember their duties and obligations, change behavior, maintain emotional stability, maintain social interactions, and apply spiritual values in order to get a good mental health in their daily activities. Keywords: Sufistic Counseling, Overcoming Game Online, Game Online